(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
In the modern world, the efficiency of a project takes a leading role in the activities of any company, it is increased by reducing costs, obtaining tax incentives, increasing the manufacturability of production, and applying innovative approaches to activities. By calculating the key performance indicators of an investment project, any event can be transferred to the plane of the economy, due to which a decision is made to start the project.